Intranasal vaccine against COVID-19 based on a recombinant variant of the Sendai virus (Paramyxoviridae: Respirovirus) strain Moscow - Gleb A. Kudrov; Sergei S. Zainutdinov; Antonina A. Grazhdantseva; Andrey V. Shipovalov; Galina F. Sivolobova; Anastasiya V. Semenova; Iuliia A. Merkuleva; Dmitry N. Shcherbakov; Oleg S. Taranov; Anna V. Zaykovskaya; Irina S. Shulgina; Oleg V. Pyankov; et al. (Вопросы вирусологии, 2023)
Introduction. Intranasal vaccination using live vector vaccines based on non-pathogenic or slightly pathogenic viruses is the one of the most convenient, safe and effective ways to prevent respiratory infections, including COVID-19. Sendai virus is the best suited for this purpose, since it is respiratory virus and is capable of limited replication in human bronchial epithelial cells without causing disease.